Fuel cell stainless steel bipolar plate and preparation method thereof
Through the combination of modified graphene and epoxy resin and heat treatment technology, the problem of insufficient corrosion resistance of fuel cell bipolar plates in high-temperature and strong acid environments is solved, the contact resistance and humidity resistance are improved, and the bipolar plates are extended. Service life and reduce maintenance costs.
Patent Information
- Application Number
- CN202411338378.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing fuel cell bipolar plates are insufficient in high-temperature and strong acid environments, resulting in reduced conductivity and damaged mechanical stability, increasing maintenance and replacement costs.
Silane modifiers are prepared by epoxy ring opening reaction and esterification reaction, graphene is modified through hydrolysis polymerization reaction and reduction reaction, combined with epoxy resin for compounding, and stainless steel bipolar plates are prepared by electrochemical deposition and heat treatment to enhance their Contact resistance, corrosion resistance, hydrophobic resistance, high temperature resistance and humidity resistance.
It significantly improves the contact resistance, corrosion resistance, adhesion, high temperature resistance and humidity resistance of stainless steel bipolar plates, extends the service life of the bipolar plates and reduces maintenance costs.
Smart Images

Figure BDA0005058930880000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cell stainless steel bipolar plates, and in particular relates to a fuel cell stainless steel bipolar plate and a preparation method thereof. Background Art
[0002] Bipolar plates are key components of proton exchange membrane fuel cells (PEMFCs). They not only conduct electricity and separate gases, but also have an important impact on the overall performance and durability of the battery. Bipolar plates have been widely studied for their cost-effectiveness and processing advantages, but they are susceptible to corrosion in the high temperature and strong acidic environment of PEMFCs, which affects the conductivity and durability of the battery. The coating technology of metal bipolar plates is the key to improving their performance. Studies have shown that the coatings of metal bipolar plates can be divided into metal coatings, non-metallic coatings and composite coatings. Among them, non-metallic coatings such as graphite-based coatings and conductive polymer coatings are simple to prepare and low in cost, becoming a hot topic for scientists.
[0003] The patent with application number CN202211617308.1 provides a method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate. A magnesium alloy with extremely low density is used as a substrate, and a corrosion-resistant coating is arranged on the surface of the substrate. The corrosion-resistant coating uses a conductive polymer such as polyaniline as a matrix material. Polyaniline has corrosion inhibition behavior and anion exchangeability. While protecting the underlying metal substrate, it can exchange anions with chloride ions in the corrosive environment to inhibit the penetration of corrosive anions. At the same time, by compounding adhesives and nano-oxides, the bonding force between the polyaniline coating and the magnesium alloy and the corrosion resistance of the coating are further improved. The preparation process of the invention is simple, the operation steps are few, and it is safe and environmentally friendly. Compared with existing metal materials such as aluminum, nickel, titanium and stainless steel, it can greatly reduce the weight of proton exchange membrane fuel cells; polyaniline-based coatings show great potential in the application of bipolar plate coatings for fuel cells due to their unique electrochemical properties and conductivity. However, the long-term corrosion resistance of polyaniline coatings in the high-temperature and strong acid environment of fuel cells still needs to be improved, which limits their large-scale application in fuel cells. The patent with application number CN202210281155.1 provides a metal bipolar plate for a fuel cell. The invention sequentially covers a first coating and a second coating on a metal substrate, wherein the first coating is a graphene layer with holes, and the second coating contains graphene oxide and polytetrafluoroethylene, and the holes are filled with graphene oxide and polytetrafluoroethylene. The graphene composite coating of the invention has the advantages of low price, good mechanical properties, corrosion resistance and excellent conductivity in the working environment of proton exchange membrane fuel cells. It can meet the use requirements of fuel cell bipolar plates and is suitable for mass production; polytetrafluoroethylene is a polymer material widely used in various industrial fields, and is well-known for its excellent chemical stability and heat resistance, but its strong chemical inertness and extremely low surface energy lead to poor adhesion of the polytetrafluoroethylene coating, which seriously limits its application in the coating field. In addition, when the proton exchange membrane fuel cell is in operation, the metal bipolar plates will be exposed to an environment of high humidity, high potential and uneven temperature distribution. These conditions will accelerate the corrosion process of the metal bipolar plates, especially in the cathode environment of high potential and high humidity. The corrosion of the metal bipolar plates is more serious. The corrosion of the metal bipolar plates will lead to increased contact resistance, affecting the conductivity of the battery, thereby reducing the output power and overall performance of the battery. It may also cause deformation or fracture of the bipolar plates, affecting the mechanical stability of the battery. Its durability will be affected, thereby increasing the cost of maintenance and replacement. Therefore, moisture and heat resistance is also particularly important for metal bipolar plates. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a fuel cell stainless steel bipolar plate and a preparation method thereof. The present invention first uses epoxy ring-opening reaction and esterification reaction to prepare a silane modifier, then uses hydrolysis polymerization reaction and reduction reaction to prepare modified graphene, and then the modified graphene and epoxy resin are compounded, and the fuel cell stainless steel bipolar plate prepared by electrochemical deposition and heat treatment has excellent contact resistance, corrosion resistance, hydrophobicity, adhesion, high temperature resistance and moisture and heat resistance.
[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0006] A method for preparing a fuel cell stainless steel bipolar plate comprises the following steps:
[0007] (1) ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding a silane modifier, raising the temperature to 55-60° C. under stirring conditions, adjusting the pH to 5-6, reacting for 3.5-4.5 hours, cooling to room temperature, separating the solid from the liquid, washing and drying the solid, and obtaining modified graphene oxide;
[0008] (2) ultrasonically dispersing the modified graphene oxide obtained in step (1) in deionized water, adding hydroiodic acid, heating to 85-90° C. under stirring, reacting for 3-4 hours, cooling to room temperature, separating the solid from the liquid, washing and drying the solid to obtain the modified graphene;
[0009] (3) ultrasonically dispersing the modified graphene obtained in step (2) in deionized water to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, mixing well, then adding epoxy resin, stirring at room temperature for 1-2 hours, and standing to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 2-4 hours, and placing in a magnetic field to stand to obtain an electrolyte solution;
[0010] (4) The pretreated stainless steel bipolar plate, the reference electrode and the auxiliary electrode are placed in an electrolyte solution, connected through a three-electrode system, and electrochemical deposition is performed using cyclic voltammetry, and then heat treated at 170-190° C. for 20-40 min to obtain a fuel cell stainless steel bipolar plate.
[0011] Further, the preparation method of the silane modifier in step (1) is:
[0012] Step S1, dispersing 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide and boric acid in toluene, mixing evenly and raising the temperature to 65-70° C., reacting for 15-18 hours under stirring, cooling to room temperature, removing the solvent, purifying, and obtaining product 1;
[0013] Step S2, dispersing quinoline-4-acetic acid in N,N-dimethylformamide, raising the temperature to 60-68° C., and then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 4-6 hours under stirring conditions, cooling to room temperature, extracting, concentrating, and drying to obtain a silane modifier.
[0014] As a new type of two-dimensional carbon nanomaterial, graphene has been widely studied for enhancing the performance of epoxy resin-based composites due to its unique physical and chemical properties, such as high electrical conductivity, high thermal conductivity and excellent mechanical properties. Epoxy resin is a thermosetting plastic with good mechanical properties, chemical stability and electrical insulation, but its poor heat resistance and high brittleness limit its application in high-performance fields. The addition of graphene and its derivatives provides new possibilities for epoxy resin-based composites in high-end applications by improving the electrical conductivity, thermal conductivity and mechanical properties of epoxy resin. However, the compatibility of conductive fillers with resins is affected by the surface functional groups of the raw materials, which directly affects the dispersion uniformity of the conductive fillers and the interface properties of the conductive fillers / resins. The invention first modifies graphene oxide by using a silane modifier, and introduces a variety of organic functional groups on the surface of graphene oxide particles by means of a hydrolysis condensation reaction to obtain modified graphene oxide; then the modified graphene oxide is subjected to a reduction reaction to obtain modified graphene; then the modified graphene and an epoxy resin are compounded to obtain an electrolyte solution; finally, a pretreated stainless steel bipolar plate, a reference electrode and an auxiliary electrode are placed in the electrolyte solution, and after electrochemical deposition and heat treatment, a fuel cell stainless steel bipolar plate is obtained; wherein the preparation method of the silane modifier is as follows: first, 4-aminobutyltriethoxysilane and 3-(perfluoro-n-hexyl)propylene oxide are used as starting materials, and an epoxy ring-opening reaction occurs under the catalysis of boric acid to obtain a product 1; the product 1 contains a hydroxyl group in its structure, and an esterification reaction occurs with quinoline-4-acetic acid under the catalysis of p-toluenesulfonic acid to obtain the product.
[0015] In order to obtain a surface functionalized and directional modified fuel cell stainless steel bipolar plate, the mass ratio of graphene oxide and silane modifier in step (1) is 1:0.55-0.75, the amount of graphene oxide added to the ethanol aqueous solution is 0.02-0.03 g / mL, and the mass fraction of ethanol in the ethanol aqueous solution is 80-90%; the mass ratio of modified graphene oxide, deionized water and hydroiodic acid in step (2) is 1:20-30:1.7-2.3; the mass ratio of modified graphene to deionized water in the preparation process of modified graphene dispersion in step (3) is 0.010-0.012:1 00, the mass ratio of glacial acetic acid, deionized water and epoxy resin in the preparation process of the activated epoxy resin is 5:300-400:60-70, and the mass ratio of modified graphene dispersion to activated epoxy resin in the preparation process of the electrolyte solution in step (3) is 0.85-1.0:1; the pretreatment (hydroxylation treatment) process of the stainless steel bipolar plate in step (4) is: ultrasonically clean the stainless steel bipolar plate in acetone, anhydrous ethanol and deionized water respectively, place it in a mixed solution of concentrated sulfuric acid and hydrogen peroxide after drying, react at 80-100°C for 1-3h, take it out and dry it.
[0016] In order to obtain a silane modifier and ensure product consistency, the molar ratio of 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid in step S1 is 1:0.9-1.0:0.16-0.22, and the mass volume ratio of 4-aminobutyltriethoxysilane to toluene is 0.15-0.20 g / mL; the mass ratio of quinoline-4-acetic acid, product 1, and p-toluenesulfonic acid in step S2 is 0.5:0.9-1.0:0.05-0.07, and the mass volume ratio of quinoline-4-acetic acid to N,N-dimethylformamide is 0.12-0.16 g / mL.
[0017] The fuel cell stainless steel bipolar plate is prepared by the above method.
[0018] The present invention has the following beneficial effects:
[0019] The present invention utilizes multi-step chemical reactions to prepare modified graphene, and introduces quinoline rings, fluorine elements, siloxanes, and alkyl chains on the surface of graphene particles. Fluorine elements are the elements with the highest electronegativity, and they can form extremely strong covalent bonds with carbon elements, and such bonds are difficult to be broken. Therefore, fluorine compounds generally have good chemical stability, are not easy to participate in electrochemical reactions, and exhibit excellent corrosion resistance in electrochemical corrosion environments; siloxanes can form chemical bonds or physical interactions with polar groups on the surface of materials, and thus can form good adhesion with the surfaces of various materials (such as glass, metal, plastic, and ceramics). The synergistic effect of siloxanes and epoxy resins can significantly improve the bonding properties of epoxy resins, and thus significantly improve the adhesion of composite materials on the surface of stainless steel bipolar plates; the combination of fluorine elements and siloxanes can also improve the hydrophobic properties of composite materials in environments with high temperature, high humidity, or chemically corrosive media; the quinoline ring has a stable conjugated system The π-π stacking effect between quinoline rings can enhance the interaction between molecules, making it difficult to decompose at high temperature, thereby making the product exhibit excellent heat resistance. In addition, the nitrogen atom on the quinoline ring carries a partial negative charge. This electron distribution helps to stabilize the molecule, making it difficult to undergo chemical reactions under wet and hot conditions, thereby improving the product's resistance to wet and hot conditions. The introduction of a variety of organic groups in the modified graphene structure can also improve the dispersibility and compatibility of inorganic particles in epoxy resin materials, effectively exerting the reinforcing effect of modified graphene, compounding the modified graphene and epoxy resin, and electrochemically depositing them under the action of a magnetic field. After heat treatment, they can form an excellent conductive network and protective layer on the surface of the stainless steel bipolar plate through mutual cross-linking, and significantly reduce the contact resistance of the stainless steel bipolar plate.
[0020] The fuel cell stainless steel bipolar plate provided by the present invention has excellent contact resistance, corrosion resistance, hydrophobicity, adhesion, high temperature resistance and moisture and heat resistance. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application. 3-(Perfluoro-n-hexyl)propylene oxide, CAS No. 38565-52-5; 4-aminobutyltriethoxysilane, CAS No. 94047-95-7; graphene oxide, thickness 0.6-1.2nm, diameter 0.8-2μm, purity 99%, purchased from Guangzhou Hongwu Materials Technology Co., Ltd.; epoxy resin, model E-51, brand Baling Petrochemical, viscosity 11000-14000 (mPa·s).
[0022] Example 1
[0023] A method for preparing a silane modifier comprises the following steps:
[0024] Step S1, dispersing 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid in toluene, mixing well, raising the temperature to 68° C., reacting for 16 hours under stirring, cooling to room temperature, distilling under reduced pressure to remove toluene, and then purifying by column chromatography (petroleum ether / ethyl acetate) to obtain product 1; wherein the molar ratio of 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid is 1:0.95:0.19, and the mass volume ratio of 4-aminobutyltriethoxysilane to toluene is 0.17 g / mL;
[0025] Step S2, dispersing quinoline-4-acetic acid in N,N-dimethylformamide, raising the temperature to 65°C, and then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 5 hours under stirring, cooling to room temperature, and then adding deionized water and ethyl acetate for extraction, taking the organic phase and concentrating it, and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a silane modifier; wherein the mass ratio of quinoline-4-acetic acid, product 1, and p-toluenesulfonic acid is 0.5:0.95:0.06, the mass volume ratio of quinoline-4-acetic acid to N,N-dimethylformamide is 0.14 g / mL, and the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate is 1:1:2.
[0026] A method for preparing a fuel cell stainless steel bipolar plate comprises the following steps:
[0027] (1) ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding a silane modifier, raising the temperature to 57° C. under stirring, adjusting the pH to 5-6 with 2 mol / L hydrochloric acid, reacting for 4 h, cooling to room temperature, separating the solid from the liquid, taking the solid, rinsing with water, and drying in a 65° C. vacuum drying oven for 12 h to obtain modified graphene oxide; wherein the mass ratio of graphene oxide to the silane modifier is 1:0.65, the amount of graphene oxide added to the ethanol aqueous solution is 0.025 g / mL, the mass fraction of ethanol in the ethanol aqueous solution is 85%, the ultrasonic power of the ultrasonic dispersion is 300 W, and the ultrasonic time is 10 min;
[0028] (2) ultrasonically dispersing the modified graphene oxide obtained in step (1) in deionized water, adding hydroiodic acid, heating to 87° C. under stirring, reacting for 3.5 h, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65° C. for 24 h to obtain modified graphene; wherein the mass ratio of modified graphene oxide, deionized water, and hydroiodic acid is 1:25:1.9, the ultrasonic power of ultrasonic dispersion is 400 W, and the ultrasonic time is 15 min;
[0029] (3) ultrasonically dispersing the modified graphene obtained in step (2) in deionized water, with an ultrasonic power of 400 W and an ultrasonic time of 15 min to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, mixing well, and then adding epoxy resin, stirring at room temperature for 1.5 hours, and letting it stand naturally for 12 hours to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 3 hours, placing it in a 15T magnetic field and letting it stand for 12 hours to obtain an electrolyte solution; wherein, in the preparation process of the modified graphene dispersion, the mass ratio of the modified graphene to the deionized water is 0.011:100, the mass ratio of the glacial acetic acid, the deionized water, and the epoxy resin in the preparation process of the activated epoxy resin is 5:350:65, and the mass ratio of the modified graphene dispersion to the activated epoxy resin in the preparation process of the electrolyte solution is 0.95:1;
[0030] (4) The pretreated stainless steel bipolar plate, the reference electrode and the auxiliary electrode are placed in an electrolyte solution and connected through a three-electrode system. In a magnetic field of 15T, the stainless steel bipolar plate is opposite to the magnetic field direction, and electrochemical deposition is performed by cyclic voltammetry, and then heat treated at 180°C for 30 minutes to obtain a fuel cell stainless steel bipolar plate; wherein the pretreatment process of the stainless steel bipolar plate is: the stainless steel bipolar plate is ultrasonically cleaned in acetone, anhydrous ethanol and deionized water in turn, the ultrasonic power is 800W, the ultrasonic time is 5 minutes, and after natural drying for 24 hours, it is placed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, the concentrated sulfuric acid concentration is 98%, the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 75:25, reacted at 90°C for 2 hours, and taken out for natural drying to obtain; the stainless steel bipolar plate is made of 316L stainless steel; the reference electrode is a calomel electrode; the auxiliary electrode is a platinum electrode; the scanning potential is -200-1200mV, the scanning speed is 30mV / s, and the number of cycles is 20 times.
[0031] Example 2
[0032] A method for preparing a silane modifier comprises the following steps:
[0033] Step S1, dispersing 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid in toluene, mixing well, raising the temperature to 65° C., reacting for 18 hours under stirring, cooling to room temperature, distilling off toluene under reduced pressure, and then purifying by column chromatography (petroleum ether / ethyl acetate) to obtain product 1; wherein the molar ratio of 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid is 1:1:0.22, and the mass volume ratio of 4-aminobutyltriethoxysilane to toluene is 0.15 g / mL;
[0034] Step S2, dispersing quinoline-4-acetic acid in N,N-dimethylformamide, raising the temperature to 60°C, and then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 6 hours under stirring, cooling to room temperature, and then adding deionized water and ethyl acetate for extraction, taking the organic phase and concentrating it, and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a silane modifier; wherein the mass ratio of quinoline-4-acetic acid, product 1, and p-toluenesulfonic acid is 0.5:1:0.07, the mass volume ratio of quinoline-4-acetic acid to N,N-dimethylformamide is 0.12 g / mL, and the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate is 1:1:2.
[0035] A method for preparing a fuel cell stainless steel bipolar plate comprises the following steps:
[0036] (1) ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding a silane modifier, raising the temperature to 55° C. under stirring, adjusting the pH to 5-6 with 2 mol / L hydrochloric acid, reacting for 4.5 h, cooling to room temperature, separating the solid from the liquid, taking the solid, rinsing it with water, and drying it in a vacuum drying oven at 65° C. for 12 h to obtain modified graphene oxide; wherein the mass ratio of graphene oxide to the silane modifier is 1:0.75, the amount of graphene oxide added to the ethanol aqueous solution is 0.02 g / mL, the mass fraction of ethanol in the ethanol aqueous solution is 90%, the ultrasonic power of the ultrasonic dispersion is 300 W, and the ultrasonic time is 10 min;
[0037] (2) ultrasonically dispersing the modified graphene oxide obtained in step (1) in deionized water, adding hydroiodic acid, heating to 85° C. under stirring, reacting for 4 h, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65° C. for 24 h to obtain modified graphene; wherein the mass ratio of modified graphene oxide, deionized water, and hydroiodic acid is 1:35:2.3, the ultrasonic power of ultrasonic dispersion is 400 W, and the ultrasonic time is 15 min;
[0038] (3) ultrasonically dispersing the modified graphene obtained in step (2) in deionized water, with an ultrasonic power of 400 W and an ultrasonic time of 15 min to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, mixing well, and then adding epoxy resin, stirring at room temperature for 1 hour, and letting it stand naturally for 12 hours to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 4 hours, placing it in a 15T magnetic field and letting it stand for 12 hours to obtain an electrolyte solution; wherein, in the preparation process of the modified graphene dispersion, the mass ratio of the modified graphene to the deionized water is 0.012:100, the mass ratio of the glacial acetic acid, the deionized water, and the epoxy resin in the preparation process of the activated epoxy resin is 5:400:70, and the mass ratio of the modified graphene dispersion to the activated epoxy resin in the preparation process of the electrolyte solution is 1:1;
[0039] (4) The pretreated stainless steel bipolar plate, the reference electrode and the auxiliary electrode are placed in an electrolyte solution and connected through a three-electrode system. In a magnetic field of 15T, the stainless steel bipolar plate is opposite to the magnetic field direction, and electrochemical deposition is performed by cyclic voltammetry. Then, the plate is heat treated at 170°C for 40 minutes to obtain a fuel cell stainless steel bipolar plate. The pretreatment process of the stainless steel bipolar plate is as follows: the stainless steel bipolar plate is ultrasonically cleaned in acetone, anhydrous ethanol and deionized water in turn, with the ultrasonic power of 800W and the ultrasonic time of 5 minutes. After natural drying for 24 hours, the plate is placed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, with the concentrated sulfuric acid concentration of 98% and the volume ratio of concentrated sulfuric acid to hydrogen peroxide being 75:25. The plate is reacted at 80°C for 3 hours, and then taken out and dried naturally to obtain a fuel cell stainless steel bipolar plate. The stainless steel bipolar plate is made of 316L stainless steel. The reference electrode is a calomel electrode. The auxiliary electrode is a platinum electrode. The scanning potential is -200-1200mV, the scanning speed is 30mV / s, and the number of cycles is 20 times.
[0040] Example 3
[0041] A method for preparing a silane modifier comprises the following steps:
[0042] Step S1, dispersing 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid in toluene, mixing well, raising the temperature to 70°C, reacting for 15 hours under stirring, cooling to room temperature, distilling under reduced pressure to remove toluene, and then purifying by column chromatography (petroleum ether / ethyl acetate) to obtain product 1; wherein the molar ratio of 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid is 1:0.9:0.16, and the mass volume ratio of 4-aminobutyltriethoxysilane to toluene is 0.20 g / mL;
[0043] Step S2, dispersing quinoline-4-acetic acid in N,N-dimethylformamide, raising the temperature to 68°C, and then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 4 hours under stirring, cooling to room temperature, and then adding deionized water and ethyl acetate for extraction, taking the organic phase and concentrating it, and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a silane modifier; wherein the mass ratio of quinoline-4-acetic acid, product 1, and p-toluenesulfonic acid is 0.5:0.9:0.05, the mass volume ratio of quinoline-4-acetic acid to N,N-dimethylformamide is 0.16 g / mL, and the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate is 1:1:2.
[0044] A method for preparing a fuel cell stainless steel bipolar plate comprises the following steps:
[0045] (1) ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding a silane modifier, raising the temperature to 60° C. under stirring, adjusting the pH to 5-6 with 2 mol / L hydrochloric acid, reacting for 3.5 h, cooling to room temperature, separating the solid from the liquid, taking the solid, rinsing it with water, and drying it in a vacuum drying oven at 65° C. for 12 h to obtain modified graphene oxide; wherein the mass ratio of graphene oxide to the silane modifier is 1:0.55, the amount of graphene oxide added to the ethanol aqueous solution is 0.03 g / mL, the mass fraction of ethanol in the ethanol aqueous solution is 80%, the ultrasonic power of the ultrasonic dispersion is 300 W, and the ultrasonic time is 10 min;
[0046] (2) ultrasonically dispersing the modified graphene oxide obtained in step (1) in deionized water, adding hydroiodic acid, heating to 90° C. under stirring, reacting for 3 h, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65° C. for 24 h to obtain modified graphene; wherein the mass ratio of modified graphene oxide, deionized water, and hydroiodic acid is 1:20:1.7, the ultrasonic power of ultrasonic dispersion is 400 W, and the ultrasonic time is 15 min;
[0047] (3) ultrasonically dispersing the modified graphene obtained in step (2) in deionized water, with an ultrasonic power of 400 W and an ultrasonic time of 15 min to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, mixing well, and then adding epoxy resin, stirring at room temperature for 2 h, and letting it stand naturally for 12 h to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 2 h, placing it in a 15T magnetic field and letting it stand for 12 h to obtain an electrolyte solution; wherein, in the preparation process of the modified graphene dispersion, the mass ratio of the modified graphene to the deionized water is 0.01:100, the mass ratio of the glacial acetic acid, the deionized water, and the epoxy resin in the preparation process of the activated epoxy resin is 5:300:60, and the mass ratio of the modified graphene dispersion to the activated epoxy resin in the preparation process of the electrolyte solution is 0.85:1;
[0048] (4) The pretreated stainless steel bipolar plate, the reference electrode and the auxiliary electrode are placed in an electrolyte solution and connected through a three-electrode system. In a magnetic field of 15T, the stainless steel bipolar plate is opposite to the magnetic field direction, and electrochemical deposition is performed by cyclic voltammetry. Then, the plate is heat treated at 190°C for 20 minutes to obtain a fuel cell stainless steel bipolar plate. The pretreatment process of the stainless steel bipolar plate is as follows: the stainless steel bipolar plate is ultrasonically cleaned in acetone, anhydrous ethanol and deionized water in turn, with the ultrasonic power of 800W and the ultrasonic time of 5 minutes. After natural drying for 24 hours, the plate is placed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, with the concentrated sulfuric acid concentration of 98% and the volume ratio of concentrated sulfuric acid to hydrogen peroxide being 75:25. The plate is reacted at 100°C for 1 hour, and then taken out and dried naturally to obtain the fuel cell stainless steel bipolar plate. The stainless steel bipolar plate is made of 316L stainless steel. The reference electrode is a calomel electrode. The auxiliary electrode is a platinum electrode. The scanning potential is -200-1200mV, the scanning speed is 30mV / s, and the number of cycles is 20 times.
[0049] Comparative Example 1
[0050] A method for preparing a silane modifier comprises the following steps:
[0051] 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide and boric acid are dispersed in toluene, mixed evenly, and then the temperature is increased to 68°C. The mixture is reacted for 16 hours under stirring, cooled to room temperature, and toluene is removed by distillation under reduced pressure. The mixture is then purified by column chromatography (petroleum ether / ethyl acetate) to obtain a silane modifier. The molar ratio of 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide and boric acid is 1:0.95:0.19, and the mass volume ratio of 4-aminobutyltriethoxysilane to toluene is 0.17 g / mL.
[0052] A method for preparing a stainless steel bipolar plate for a fuel cell is prepared according to the method described in Example 1.
[0053] Comparative Example 2
[0054] A method for preparing a fuel cell stainless steel bipolar plate is prepared according to the method described in Example 1, except that the silane modifier in step (1) is replaced by 4-aminobutyltriethoxysilane.
[0055] The fuel cell stainless steel bipolar plates prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to relevant performance tests. The contact resistance and corrosion current density tests were conducted in accordance with GB / T20042.6-2011 "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Methods", with the contact resistance test pressure at 1.4 MPa and the corrosion current density test using a three-electrode electrochemical test system, with the solution being 0.5 M H2SO4 + 5 ppm HF solution, temperature is 80℃, working voltage is 0.6V; the hydrophobic performance test is carried out using KRUSSDSA100 contact angle meter, and the amount of water dripped each time is 10μL; the adhesion performance test is carried out in accordance with GB / T9286-2021 "Scratch test for paints and varnishes", and the scratch spacing is 1mm; the high temperature resistance performance test is carried out in accordance with GB / T1735-2009 "Determination of heat resistance of paints and varnishes", and the sample is placed at a temperature of 280℃ for 4h, and the sample state is observed; the moisture and heat resistance performance test is carried out in accordance with GB / T1740-2007 "Determination of moisture and heat resistance of paint films"; the above tests are carried out three times and the average value is taken. The test results are shown in Table 1. It can be seen from Table 1 that the contact resistance, corrosion resistance, hydrophobicity, high temperature resistance and moisture and heat resistance of the fuel cell stainless steel bipolar plates prepared in Examples 1-3 are significantly better than those in Comparative Examples 1-2; it can be seen from the data of Example 1 and Comparative Example 2 that the silane coupling agent is modified in two steps to obtain a silane modifier, which is then grafted onto the surface of graphene to obtain an organically modified graphene, which is compounded with an activated epoxy resin and deposited on the surface of the stainless steel bipolar plate using cyclic voltammetry, and the prepared fuel cell stainless steel bipolar plate has relatively excellent comprehensive performance.
[0056] Table 1 Fuel cell stainless steel bipolar plate related performance test results
[0057]
[0058] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a fuel cell stainless steel bipolar plate, characterized in that: The following steps are involved: (1) ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding a silane modifier, raising the temperature to 55-60° C. under stirring conditions, adjusting the pH to 5-6, reacting for 3.5-4.5 hours, cooling to room temperature, separating the solid from the liquid, washing and drying the solid, and obtaining modified graphene oxide; (2) ultrasonically dispersing the modified graphene oxide obtained in step (1) in deionized water, adding hydroiodic acid, heating to 85-90° C. under stirring, reacting for 3-4 hours, cooling to room temperature, separating the solid from the liquid, washing and drying the solid to obtain the modified graphene; (3) ultrasonically dispersing the modified graphene obtained in step (2) in deionized water to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, mixing well, then adding epoxy resin, stirring at room temperature for 1-2 hours, and standing to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 2-4 hours, and placing in a magnetic field to stand to obtain an electrolyte solution; (4) The pretreated stainless steel bipolar plate, the reference electrode and the auxiliary electrode are placed in an electrolyte solution, connected through a three-electrode system, and electrochemical deposition is performed using cyclic voltammetry, and then heat treated at 170-190° C. for 20-40 min to obtain a fuel cell stainless steel bipolar plate.
2. The method for preparing a fuel cell stainless steel bipolar plate according to claim 1, characterized in that: The preparation method of the silane modifier described in step (1) is: Step S1, dispersing 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide and boric acid in toluene, mixing evenly and raising the temperature to 65-70° C., reacting for 15-18 hours under stirring, cooling to room temperature, removing the solvent, purifying, and obtaining product 1; Step S2, dispersing quinoline-4-acetic acid in N,N-dimethylformamide, raising the temperature to 60-68° C., and then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 4-6 hours under stirring conditions, cooling to room temperature, extracting, concentrating, and drying to obtain a silane modifier.
3. The method for preparing a fuel cell stainless steel bipolar plate according to claim 1, characterized in that: The mass ratio of graphene oxide to silane modifier in step (1) is 1:0.55-0.75, the amount of graphene oxide added to the ethanol aqueous solution is 0.02-0.03 g / mL, and the mass fraction of ethanol in the ethanol aqueous solution is 80-90%.
4. The method for preparing a fuel cell stainless steel bipolar plate according to claim 1, characterized in that: The mass ratio of the modified graphene oxide, deionized water and hydroiodic acid in step (2) is 1:20-30:1.7-2.
3.
5. The method for preparing a fuel cell stainless steel bipolar plate according to claim 1, characterized in that: In the step (3), the mass ratio of modified graphene to deionized water in the preparation process of the modified graphene dispersion is 0.010-0.012:100, and the mass ratio of glacial acetic acid, deionized water and epoxy resin in the preparation process of the activated epoxy resin is 5:300-400:60-70.
6. The method for preparing a fuel cell stainless steel bipolar plate according to claim 1, characterized in that: In the electrolyte solution preparation process in step (3), the mass ratio of the modified graphene dispersion to the activated epoxy resin is 0.85-1.0:
1.
7. The method for preparing a fuel cell stainless steel bipolar plate according to claim 1, characterized in that: The pretreatment process of the stainless steel bipolar plate in step (4) is as follows: ultrasonically clean the stainless steel bipolar plate in acetone, anhydrous ethanol, and deionized water respectively, place it in a mixed solution of concentrated sulfuric acid and hydrogen peroxide after drying, react at 80-100° C. for 1-3 hours, take it out and dry it.
8. The method for preparing a fuel cell stainless steel bipolar plate according to claim 2, characterized in that: The molar ratio of 4-aminobutyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide and boric acid in step S1 is 1:0.9-1.0:0.16-0.22, and the mass volume ratio of 4-aminobutyltriethoxysilane to toluene is 0.15-0.20 g / mL.
9. The method for preparing a fuel cell stainless steel bipolar plate according to claim 2, characterized in that: The mass ratio of quinoline-4-acetic acid, product 1, and p-toluenesulfonic acid in step S2 is 0.5:0.9-1.0:0.05-0.07, and the mass volume ratio of quinoline-4-acetic acid to N,N-dimethylformamide is 0.12-0.16 g / mL.
10. A fuel cell stainless steel bipolar plate, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing silane / epoxy resin-GO-silane multilayer protective film covering metal surface
CN109338430A
Preparation method of fuel cell bipolar plate surface microstructure
CN114122422A
Composite protective coating for metal bipolar plate and preparation method of composite protective coating
CN117334944A